2016
DOI: 10.7759/cureus.783
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Severe Takotsubo Cardiomyopathy Associated with 5-Fluorouracil in a Patient with Abnormalities of Both Dihydropyrimidine Dehydrogenase (DPYD) and Thymidylate Synthase (TYMS) Genes

Abstract: 5-Fluorouracil (5-FU) is the backbone of the chemotherapy regimens approved for treatment of many malignancies, especially colorectal cancer (CRC). The incidence of cardiotoxicity associated with 5-FU ranges between 1.5% to 18% and is most commonly manifested as anginal symptoms. Cardiomyopathy is very rarely reported with 5-FU and capecitabine. A 35-year-old Caucasian male with T3, N1, M0 rectal cancer after the initial neoadjuvant chemoradiation with 5FU/LV followed by surgical abdominoperineal resection (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…It is probable that 5-FU cardiotoxicity may be much more common and clinically significant than previously reported as awareness has risen due to continued use, many 5-FU based regimens, longer duration on therapy, and availability of novel agents. 2,42,43 Although the history of pre-existing coronary artery disease may increase the risk of cardiac toxicity associated with 5-FU/capecitabine, the published data does not seem to In second-line treatment after 5-FU failure, IROX was found to be superior to irinotecan monotherapy. 31 Not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable that 5-FU cardiotoxicity may be much more common and clinically significant than previously reported as awareness has risen due to continued use, many 5-FU based regimens, longer duration on therapy, and availability of novel agents. 2,42,43 Although the history of pre-existing coronary artery disease may increase the risk of cardiac toxicity associated with 5-FU/capecitabine, the published data does not seem to In second-line treatment after 5-FU failure, IROX was found to be superior to irinotecan monotherapy. 31 Not reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that 5-FU cardiotoxicity may be much more common and clinically significant than previously reported as awareness has risen due to continued use, many 5-FU based regimens, longer duration on therapy, and availability of novel agents. 2 , 42 , 43 Although the history of pre-existing coronary artery disease may increase the risk of cardiac toxicity associated with 5-FU/capecitabine, the published data does not seem to underline the predictive value of the presence of cardiac risk factors for the development of 5-FU-induced cardiac side-effects. Therefore, caution must be taken in treating these patients and if any signs or symptoms suggest cardiotoxicity, the drug should be suspended and a thorough work-up must be performed with multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in molecular and genetic epidemiology have increased our knowledge on the mechanisms behind colorectal carcinogenesis, the relationship between disease susceptibility and exposure to carcinogens, and individual genetic variations (Gutiérrez et al, 2016). Several relevant studies have associated different polymorphisms of enzymes that metabolize drugs, such as TS and DPD as the drug target enzymes, with clinical outcomes treated with commonly prescribed drugs in chemotherapy, such as 5-FU and capecitabine (Leung & Chan, 2015;Wang et al, 2016;Romiti et al, 2016;Saif et al, 2016;Yang et al, 2016;Lee et al, 2016). Studies have demonstrated that the underexpression of TYMS predicts that patients carrying the 2R allele who are treated with capecitabine to be at an increased risk for severe fluoropyrimidine-associated toxicity (Meulendijks et al, 2016) and with an increased severity and susceptibility to various diseases (Bezerra et al, 2014;Dunna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, the significant inverse association between the 5-FU toxicity and number of 28bp tandem repeats in 5'UTR region of TYMS gene was reported by some authors [4,26,27]. In the Saif 's case report, they have described the first case of severe takotsubo cardiomyopathy related to DPD deficiency (heterozygous for the c.85T>C mutation) and homozygous polymorphism of TYMS (TSER*2/ TSER*2, 2R/2R) in a patient with colon cancer following 5-FU containing regimen [28]. Despite controversy in the literature, overall TSER*2/TSER*2 finding predicts improved survival of patients receiving 5-FU chemotherapy but also increases the risk for 5-FU toxicity.…”
Section: Table 4 Distribution Of Combined Genotypes Of 5'utr Tser Rementioning
confidence: 93%